A Rare Case Series of Vaginal Melanoma- experience of National Cancer Institute Sri Lanka - Wijeratne, YMTY; Hapuachchige, HDKC; Kannangara, S (Asian Pacific Journal of Cancer Care, 2022)
Vaginal melanomas are extremely rare gynaecological malignancy with aggressive behavior resulting in poor outcome. The aetiology is not well understood so far. There is no standardized treatment owing to the extreme rarity of the disease, however surgical excision with adjuvant radiotherapy has been the widely practiced treatment. The role of lymphadenectomy is controversial. The six cases reported between November 2015 to November 2021 at the National cancer institute Sri Lanka were treated primarily by surgical excision including hysterocolpectomy, colpectomy, and wide local excision. Pelvic lymphadenectomy was not done in most cases. Only one patient has received adjuvant radiotherapy. Only one patient died during the follow-up and 2 had recurrences.